Pediatric neuromuscular disease: study of patients assisted at the Pediatric Pneumology department of the Pereira Rossell Pediatric Hospital during 1/6/2006-31/12/2019 (Archives of Pediatrics of Uruguay, 2021)
Neuromuscular diseases (NMD) affect the different components of the motor system. As of diagnosis, they should be followed by an interdisciplinary team, in which pediatric pulmonologists play an important role in assessing the loss of muscle strength when NMD affects the respiratory or upper airway muscles.Objectives: to learn about the different neuromuscular diseases treated at the Pereira Rossell Hospital Center, to analyze the characteristics of this population and to describe the results of the main studies requested by the pediatric pulmonology clinic.Methodology: descriptive, analytical and retrospective study of patients with neuromuscular disease treated at the Pereira Rossell Hospital Center between 6/1/2006 and 12/31/2019.Results: the most frequent neuromuscular pathologies were muscular dystrophies, myopathies, Steinert’s myotonic dystrophy and spinal muscular atrophy. 21/73 patients did not have a definitive diagnosis. Spirometry showed a restrictive alteration in most of the patients. To rule out respiratory sleep disorders, nocturnal oximetry with blood gas was performed upon awakening, with nocturnal hypoventilation and obstructive apneas being the alterations found. In 12/73 non-invasive ventilation was applied.Conclusions: patients with NMD experience a progressive deterioration of respiratory function that contributes to a high rate of morbidity and mortality. Regular evaluation and monitoring of respiratory function, along with sleep studies, are essential for the timely initiation of non-invasive ventilation.Conclusions: patients with NMD experience a progressive deterioration of respiratory function that contributes to a high rate of morbidity and mortality. Regular evaluation and monitoring of respiratory function, along with sleep studies, are essential for the timely initiation of non-invasive ventilation.
Keywords: Neuromuscular diseases; Hypoventilation; Noninvasive ventilation